ADHESIVE WEAR MECHANISM AT FRICTION - Artemchuk, V. V.; Hrichanyi, M. A.; Lemeshev, O. V. (Science and Transport Progress, 2009)
The questions of mechanism of adhesion wear are considered in the article. The action of this type of wear is presented on the example of work of spring-friction shock absorber.